Isolamento e identificação de microrganismos potencialmente patogênicos em leite caprino - Ramos, Carlos Ticiano Coutinho (2015)
The goats subclinical mastitis causes economic losses due to disposal, spending on therapeutic measures and reducing the quantity and quality of milk and its derivatives. This study aimed to determine the incidence, etiology of subclinical mastitis and identify coagulase negative Staphylococcus (CNS) by PCR and identify the presence of ECN methicillin resistant or biofilm production beyond, note the risk factors associated with infection. In this study, 372 samples of goat milk fresh from 186 animals from 10 dairy farms in the state of Paraiba, were evaluated by testing the screened mug, California Mastitis Test (CMT) and bacteriological examination. After the results of the microbiological, the 24 milk samples showed that Staphylococcus coagulase negative were sent to the molecular biology laboratory of the Embrapa Coastal Tablelands for DNA extraction directly from milk. The fragments containing the genes of interest were amplified from genomic DNA isolated strains by PCR using primers specific for the amplification of genes in study. In the test the screened mug and CMT, 3.22% and 43.90% of the samples were positive, respectively. In bacteriological examination, 19.35% for the number of glands and 38.70% of the goats were positive and the most common pathogen among pure alone or in combination was coagulase negative Staphylococcus (28.25%). Make frequent cleaning the premises, isolate sick animals, have milking parlor hygiene and ceilings before milking were the biggest risks associated with infection of the mammary gland of goats. Based on this study can further the study of the etiology of subclinical mastitis goat, allowing perform extractions directly from milk samples and presenting different types of bacteria.